2023
DOI: 10.3390/cancers15030947
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Immune Checkpoint Inhibitor and Tyrosine Kinase Inhibitor Combination Therapy for Advanced or Metastatic Renal Cell Carcinoma: A Multicenter Retrospective Real-World Cohort Study

Abstract: We evaluated the efficacy and safety of combination therapy with immune checkpoint inhibitors (ICIs) and tyrosine kinase inhibitors (TKI) as first-line therapy for patients diagnosed as having advanced or metastatic renal cell carcinoma (mRCC). We enrolled 51 patients to receive ICI+TKI therapy for mRCC at 9 Japanese institutions. The overall survival (OS) of the patients treated with ICI+TKI was the primary endpoint., and the secondary endpoints were progression-free survival (PFS), objective response rate (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…A pilot study involving 10 HCC patients with vascular infiltration showed that after treatment with anti-PD-1 antibody combined with VEGFR-targeted TKI, 7 patients achieved PR, 3 patients achieved CR, and all 10 patients underwent surgery with a recurrence-free survival rate of 75% within 12 months [22]. Another study also indicated that this conversion therapy strategy can be effective and safe for hepatectomy after careful preparation and patient evaluation [23]. At the same time, A + T combination treatment of renal cell carcinoma and non-small cell lung cancer also has an excellent tumour reduction effect with a high ORR [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…A pilot study involving 10 HCC patients with vascular infiltration showed that after treatment with anti-PD-1 antibody combined with VEGFR-targeted TKI, 7 patients achieved PR, 3 patients achieved CR, and all 10 patients underwent surgery with a recurrence-free survival rate of 75% within 12 months [22]. Another study also indicated that this conversion therapy strategy can be effective and safe for hepatectomy after careful preparation and patient evaluation [23]. At the same time, A + T combination treatment of renal cell carcinoma and non-small cell lung cancer also has an excellent tumour reduction effect with a high ORR [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The use of various combination regimens with these agents has notably contributed to improved efficacy of treatment for patients with mRCC (4-8). The increase in therapeutic options has enabled the selection of treatment approaches that are expected to be effective for patients with diverse backgrounds (18,19). While the number of treatment options has increased, selecting the most appropriate therapy can be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…For the combination of avelumab (AVE) and axitinib (AXI), AVE was administered intravenously every 2 weeks, whereas AXI was administered orally twice daily [ 5 , 24 ]. Regarding the pembrolizumab (PEM) + AXI regimen, PEM was administered intravenously at a single dose of 200 or 400 mg, whereas AXI was administered orally at 5 mg twice daily [ 6 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…When the treatment regimen comprised NIVO and cabozantinib (CABO), NIVO was administered intravenously at a dose of 240 or 480 mg, whereas CABO was administered orally at 40 mg once daily [ 7 , 13 ]. For those receiving PEM and lenvatinib (LEN), PEM was administered intravenously at a dose of 200 or 400 mg, whereas LEN was administered orally at 20 mg once daily [ 8 , 13 , 24 ]. ICI therapy was discontinued after 2 years in patients treated with ICI + MTT.…”
Section: Methodsmentioning
confidence: 99%